Berperankah Audit Internal Dalam Pencegahan Fraud: Studi Pada Perusahaan Konstruksi PT. LPS - Arianto, Levana Andaiaanti; Suryani, Pesi; Kuswanti, Eko (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The role of A good internal audit in a company can increase control over the possibility of fraud and increase company value, therefore internal audit must have the competence and professionalism to carry out its duties and functions properly. This study aims to determine the role of internal audit in preventing fraud at a construction company in Surabaya. This study used a qualitative research method with a descriptive approach with semi-structured interviews. In this study, the authors used data sources obtained from primary and secondary data. Primary data is in the form of data obtained directly through interviews which are then processed by the author while secondary data is data from various existing sources. The general problem that usually occurs within the company is that there are still cases of fraud that can threaten business continuity. Fraud can be committed by external parties or internal parties only for the sake of profit. When an internal audit can carry out its role properly, the possibility of fraud can be prevented. The results of this study indicate that there is still a problem of fraud, namely the weak role of internal audit in the company, causing losses.